Preparation and Characterization of P(3HB-co-HHX)/Silk Fibroin Nanofiber for Chondrogenic Differentiation on Human Adipose Mesenchymal Stem Cell - Pramono, Andri Pramesyanti; Yulianti, Retno; Razi, Muhamad Alif; Karina; Ang, Shaik Ling; Sudesh, Kumar; Hanan; Endarwati, Yuni Cahya; Ghoza, Muhammad Radian (HAYATI Journal of Biosciences, 2026)
This study explored the proliferative and chondrogenic diﬀerentiation capacities of nanofiber containing silk fibroin hybrid Bombyx mori silkworm cocoons (Japan-China SP-01 variant from Indonesia) and PHA P(3HB-co-3HHx) on human adipose mesenchymal stem cells. First, the scaffolds were prepared for electrospinning by combining two distinct biomaterials, consisting of silk fibroin derived from hybrid Bombyx mori silkworm cocoons, with a combination of 3-hydroxybutyrate (3HB) and 3-hydroxyhexanoate (3HHx). The effects of various ratios of P(3HB-co-3HHx)/Silk Fibroin nanofiber mixture on proliferative and differentiation capacity were then investigated. Following that, the morphology, chemical compositions, contact angle, tensile strength, roughness, cell viability, and human adipose mesenchymal stem cell differentiation of the nanofiber were investigated by collagen type 2 gene expression. The results of scanning electron microscopy showed the mean diameter of the nanofiber ranged from 370-600  nm. Following that, 16,000 volts was prominent for nanofiber manufacture in all ratios. It was also demonstrated that the nanofiber has significant mechanical properties, acceptable hydrophilicity and smoothness, and appropriate cell viability (up to 99.1% compared to the control on silk fibroin nanofiber). Although PHA increased tensile strength, silk fibroin administration to the mixture predominantly enhanced chondrogenic differentiation, as evidenced by modulation of chondrogenic collagen type 2 (up to 8.718-fold) gene markers. Furthermore, the physicochemical characteristics of the nanofiber mixture significantly influenced the proliferation and differentiation of human adipose mesenchymal stem cells. The results of the tests showed that silk fibroin administration into a nanofiber mixture has improved chondrogenesis and showed great potential as a cartilage tissue scaffold.